Techno-Economic Analysis of Diesel Rotary Ups Implementation in Power Supply of Pertamina EP Zone 9 - Andi Hertanto Eka Putra; Zainal Arifin (Departemen Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2026)
This study aims to identify potential power supply design options at PT Pertamina EP Zone 9, specifically in the Tanjung and Sangatta Fields, analyse the technical and financial conditions before and after Diesel Rotary Uninterruptible Power Supply (DRUPS) implementation in Tanjung, and determine the most suitable design to enhance power reliability in Sangatta. Conducted from December 2024 to February 2025, the research uses a mixed-methods approach combining quantitative and qualitative analysis. Data collection involved direct observation, interviews, and document analysis, followed by technical and economic evaluation using ETAP simulations, power reliability indices, and investment feasibility assessments. The results show that implementing DRUPS significantly improved both operational efficiency and power supply reliability. Electricity cost savings reached 63%, and the System Average Interruption Frequency Index (SAIFI) dropped from 10.1 to 6.6 incidents per month, indicating enhanced supply stability. From an economic standpoint, DRUPS proved highly viable with BCR of 19.9, NPV of IDR 531 billion, IRR of 131.6%, and Payback Period of just one month. These findings demonstrate that DRUPS is not only technically effective but also offers rapid return on investment, making it a sustainable and strategic solution for the long-term energy needs of Pertamina EP Zone 9.